Inhibitory actions by ibandronate sodium, a nitrogen-containing bisphosphonate, on calcium-activated potassium channels in Madin–Darby canine kidney cells. (2015) - Wu, Sheng-Nan; Chen, Hui-Zhen; Chou, Yu-Hung; Huang, Yan-Ming; Lo, Yi-Ching
Abstract: The nitrogen-containing bisphosphonates used for management of the patients with osteoporosis were reported to influence the function of renal tubular cells. However, how nitrogen-containing bisphosphates exert any effects on ion currents remains controversial. The effects of ibandronate (Iban), a nitrogen-containing bisphosphonate, on ionic channels, including two types of Ca 2+ -activated K + (KCa ) channels, namely, large-conductance KCa (BKCa ) and intermediate-conductance KCa (IKCa ) channels, were investigated in Madin–Darby canine kidney (MDCK) cells. In whole-cell current recordings, Iban suppressed the amplitude of voltage-gated K + current elicited by long ramp pulse. Addition of Iban caused a reduction of BKCa channels accompanied by a right shift in the activation curve of BKCa channels, despite no change in single-channel conductance. Ca 2+ sensitivity of these channels was modified in the presence of this compound; however, the magnitude of Iban-mediated decrease in BKCa -channel activity under membrane stretch with different negative pressure remained unchanged. Iban suppressed the probability of BKCa -channel openings linked primarily to a shortening in the slow component of mean open time in these channels. The dissociation constant needed for Iban-mediated suppression of mean open time in MDCK cells was 12.2 μM. Additionally, cell exposure to Iban suppressed the activity of IKCa channels, and DC-EBIO or 9-phenanthrol effectively reversed its suppression. Under current-clamp configuration, Iban depolarized the cells and DC-EBIO or PF573228 reversed its depolarizing effect. Taken together, the inhibitory action of Iban on KCa -channel activity may contribute to the underlying mechanism of pharmacological or toxicological actions of Iban and its structurally similar bisphosphonates on renal tubular cells occurring in vivo .